2021
DOI: 10.1021/acsomega.1c03019
|View full text |Cite
|
Sign up to set email alerts
|

Porous Cobalt Sulfide Selenium Nanorods for Electrochemical Hydrogen Evolution

Abstract: A key process in electrochemical energy technology is hydrogen evolution reaction (HER). However, its electrochemical properties mainly depend on the catalytic activity of the material itself. Therefore, it is important to find efficient electrocatalysts to realize clean hydrogen production. As a typical kind of catalytic materials, transition metal dichalcogenides (TMCs) play important roles in the field of energy catalysis. As a representative of TMCs, cobalt disulfide (CoS 2 ), recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Previous reports have demonstrated that incorporating or doping transition metal sulfides, such as nickel cobalt sulfides with iron, induces lattice strain which results in peak broadening [56]. A small shift towards lower angles of the experimental diffractograms of selenium-containing samples versus the simulated diffractograms of the sulfur-only analogues can be ascribed to a larger lattice spacing which is caused by the larger radius of selenium compared to sulfur [57]. A shift in the peak positions between experimental and simulated diffractograms is also obtained if the sample is not properly aligned with the goniometer axis, e.g., by placing too thick a sample on the sample holder in the Bragg-Brentano geometry [58].…”
Section: Synthesis and Analysismentioning
confidence: 89%
“…Previous reports have demonstrated that incorporating or doping transition metal sulfides, such as nickel cobalt sulfides with iron, induces lattice strain which results in peak broadening [56]. A small shift towards lower angles of the experimental diffractograms of selenium-containing samples versus the simulated diffractograms of the sulfur-only analogues can be ascribed to a larger lattice spacing which is caused by the larger radius of selenium compared to sulfur [57]. A shift in the peak positions between experimental and simulated diffractograms is also obtained if the sample is not properly aligned with the goniometer axis, e.g., by placing too thick a sample on the sample holder in the Bragg-Brentano geometry [58].…”
Section: Synthesis and Analysismentioning
confidence: 89%
“…Sample Pd-MS5 showed the presence of 5.25 at% of Pd along with 26.16 at% of Mo and 67.59 at% of S. Heteroatom doping also caused the creation of sulfur vacancies (SVs) in the host system. 12,29,30 The created sulfur vacancies in the Pd-doped MoS 2 samples was experimentally conrmed by EDS analysis. A slight decrement of the S element in the Pd-doped MoS 2 samples as compared to pristine MoS 2 was revealed by the element stoichiometry analysis (Table SI2 †).…”
Section: Resultsmentioning
confidence: 99%